BRAC Education Program (BEP) NFPE phase III: work-plan for January-December 2001 - BRAC (© BRAC, 2016)
1. Summary of work plan 2. Introduction 3. Logical Framework (LFA) 4. Plan of acivities 5. Annexure 6. Budget supplement